Large City Architecture: the mereological mode of the quantified city. (18th December 2017) - Köhler, Daniel
Abstract: With the reading of Ludwig Hilberseimer's Grosz-stadt-Architektur simply as "Large City Architecture, " the description of the city changes from a notion of political intervention to one of quantitative examination. Thereby and when the urban is defined as "being situated in a city, " urbanism can be extended with schemata of the design of the city itself: the resonance of its parts, its mereological compositions. In such a reading, architectural knowledge overlaps with digital thought. A mereological examination of the city, based on quantitative methods allows an interface to technical, digital representations of places and buildings. This is different to common incorporations of the digital in urban design, which mainly focuses on continuous, morphological differentiations. BIM-models can be described as the nesting and incorporation of multiple representations of objects and algorithms. However, today's models focus only on the internal organization of one object, not its assembly. Through a digital reading of part-conditions in historic city models, this paper opens the possibility to enrich the evolving, and so far technocratic representations of places and buildings with the architectural knowledge of the city and its history. Abstract :